Cosine Exponential Formulation

From ProofWiki
Jump to navigation Jump to search

Theorem

For any complex number $z \in \C$:

$\cos z = \dfrac {\map \exp {i z} + \map \exp {-i z} } 2$

where:

$\exp z$ denotes the exponential function
$\cos z$ denotes the complex cosine function
$i$ denotes the inaginary unit.


Real Domain

This result is often presented and proved separately for arguments in the real domain:


$\cos x = \dfrac {e^{i x} + e^{-i x} } 2$


Proof 1

Recall the definition of the cosine function:

\(\displaystyle \cos z\) \(=\) \(\displaystyle \sum_{n \mathop = 0}^\infty \paren {-1}^n \frac {z^{2 n} } {\paren {2 n}!}\)
\(\displaystyle \) \(=\) \(\displaystyle 1 - \frac {z^2} {2!} + \frac {z^4} {4!} - \frac {z^6} {6!} + \cdots + \paren {-1}^n \frac {z^{2 n} } {\paren {2 n}!} + \cdots\)


Recall the definition of the exponential as a power series:

\(\displaystyle \exp z\) \(=\) \(\displaystyle \sum_{n \mathop = 0}^\infty \frac {z^n} {n!}\)
\(\displaystyle \) \(=\) \(\displaystyle 1 + \frac z {1!} + \frac {z^2} {2!} + \frac {z^3} {3!} + \cdots + \frac {z^n} {n!} + \cdots\)


Then, starting from the right hand side:

\(\displaystyle \frac {\exp \paren {i z} + \exp \paren {-i z} } 2\) \(=\) \(\displaystyle \frac 1 2 \paren {\sum_{n \mathop = 0}^\infty \frac {\paren {i z}^n} {n!} + \sum_{n \mathop = 0}^\infty \frac {\paren {-i z}^n} {n!} }\)
\(\displaystyle \) \(=\) \(\displaystyle \frac 1 2 \sum_{n \mathop = 0}^\infty \paren {\frac {\paren {i z}^n + \paren {-i z}^n} {n!} }\) Cosine Function is Absolutely Convergent
\(\displaystyle \) \(=\) \(\displaystyle \frac 1 2 \sum_{n \mathop = 0}^\infty \paren {\frac {\paren {i z}^{2 n} + \paren {-i z}^{2 n} } {\paren {2 n}!} + \frac {\paren {i z}^{2 n + 1} + \paren {-i z}^{2 n + 1} } {\paren {2 n + 1}!} }\) split into even and odd $n$
\(\displaystyle \) \(=\) \(\displaystyle \frac 1 2 \sum_{n \mathop = 0}^\infty \frac {\paren {i z}^{2 n} + \paren {-i z}^{2 n} } {\paren {2 n}!}\) $\paren {-i z}^{2 n + 1} = -\paren {i z}^{2 n + 1}$
\(\displaystyle \) \(=\) \(\displaystyle \frac 1 2 \sum_{n \mathop = 0}^\infty \frac {2 \paren {i z}^{2 n} } {\paren {2 n}!}\) $\left({ -1 }\right)^{2n} = 1$
\(\displaystyle \) \(=\) \(\displaystyle \sum_{n \mathop = 0}^\infty \frac {\paren {i z}^{2 n} } {\paren {2 n}!}\) cancel $2$
\(\displaystyle \) \(=\) \(\displaystyle \sum_{n \mathop = 0}^\infty \paren {-1}^n \frac {z^{2 n} } {\paren {2 n}!}\) $i^{2 n} = \paren {-1}^n$
\(\displaystyle \) \(=\) \(\displaystyle \cos z\)

$\blacksquare$


Proof 2

Recall Euler's Formula:

$\exp \paren {i z} = \cos z + i \sin z$


Then, starting from the right hand side:

\(\displaystyle \frac {\exp \paren {i z} + \exp \paren {-i z} } 2\) \(=\) \(\displaystyle \frac {\cos z + i \sin z + \cos \paren {-z} + i \sin \paren {-z} } 2\)
\(\displaystyle \) \(=\) \(\displaystyle \frac {\cos z + \cos \paren {-z} } 2\) Sine Function is Odd
\(\displaystyle \) \(=\) \(\displaystyle \frac {2 \cos z} 2\) Cosine Function is Even
\(\displaystyle \) \(=\) \(\displaystyle \cos z\)

$\blacksquare$


Proof 3

\((1):\quad\) \(\displaystyle \exp \paren {i z}\) \(=\) \(\displaystyle \cos z + i \sin z\) Euler's Formula
\((2):\quad\) \(\displaystyle \exp \paren {-i z}\) \(=\) \(\displaystyle \cos z - i \sin z\) Euler's Formula: Corollary
\(\displaystyle \leadsto \ \ \) \(\displaystyle \exp \paren {i z} + \exp \paren {-i z}\) \(=\) \(\displaystyle \paren {\cos z + i \sin z} + \paren {\cos z - i \sin z}\) $(1) + (2)$
\(\displaystyle \) \(=\) \(\displaystyle 2 \cos z\) simplifying
\(\displaystyle \leadsto \ \ \) \(\displaystyle \frac {\exp \paren {i z} + \exp \paren {-i z} } 2\) \(=\) \(\displaystyle \cos z\)

$\blacksquare$


Also presented as

This result can also be presented as:

$\cos z = \dfrac 1 2 \paren {e^{-i z} + e^{i z} }$


Also see


Sources